2018
DOI: 10.1007/s00198-017-4354-z
|View full text |Cite
|
Sign up to set email alerts
|

Bone density and microarchitecture in hepatitis C and HIV-coinfected postmenopausal minority women

Abstract: HIV+/HCV+ postmenopausal women had significantly lower spine aBMD and vBMD. These deficits in vBMD may contribute to bone fragility and excess fractures reported in HIV+/HCV+ women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Therefore, strict measures are needed to guard against osteoporosis in terms of regular screening after the age of 50 years using a DEXA scan [ 16 , 17 ], as the risk of HCV affecting BMD is more pronounced in postmenopausal women [ 56 ]. Importantly, Bedimo et al showed that even before the onset of cirrhosis, chronic HCV infection is an independent risk factor for osteoporosis and fractures among PLWHIV [ 57 ]. Carlo et al concluded that vitamin D deficiency might influence liver disease progression in HIV/HCV-coinfected patients [ 58 ].…”
Section: Impact Of Hepatitis C On Bonesmentioning
confidence: 99%
“…Therefore, strict measures are needed to guard against osteoporosis in terms of regular screening after the age of 50 years using a DEXA scan [ 16 , 17 ], as the risk of HCV affecting BMD is more pronounced in postmenopausal women [ 56 ]. Importantly, Bedimo et al showed that even before the onset of cirrhosis, chronic HCV infection is an independent risk factor for osteoporosis and fractures among PLWHIV [ 57 ]. Carlo et al concluded that vitamin D deficiency might influence liver disease progression in HIV/HCV-coinfected patients [ 58 ].…”
Section: Impact Of Hepatitis C On Bonesmentioning
confidence: 99%